2015
DOI: 10.1111/ceo.12478
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of predicted refraction with multifocal intraocular lenses using two biometry measurement devices and multiple intraocular lens power calculation formulas

Abstract: Background: To evaluate the accuracy of predicted refraction using multifocal intraocular lenses (IOLs) with power calculation based on two biometric devices and multiple IOL power calculation formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 24 publications
2
42
0
1
Order By: Relevance
“…[16] All five formulas achieved above 92% of eyes within ±1.00 D of the predicted refraction, much higher than the 85% suggested by Gale et al [25] Recent studies reported that the Barrett Universal II formula was more accurate and showed the better refractive outcomes than the other formulas. [16,[17][18][19]26] One large population study assessed the Barrett Universal II formula over the entire AL range and showed that this formula had the lowest MAE and SD of the prediction error and a higher percentage of eyes with prediction errors within ±0.25 D, ±0.50 D, and ±1.00 D, which was congruent with our findings. [18] In our study, the Barrett Universal II formula had the lowest median absolute error (0.263) and a higher percentage of eyes with prediction errors within ±0.50 D, ±0.75 D, and ±1.00 D compared to the other formulas.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[16] All five formulas achieved above 92% of eyes within ±1.00 D of the predicted refraction, much higher than the 85% suggested by Gale et al [25] Recent studies reported that the Barrett Universal II formula was more accurate and showed the better refractive outcomes than the other formulas. [16,[17][18][19]26] One large population study assessed the Barrett Universal II formula over the entire AL range and showed that this formula had the lowest MAE and SD of the prediction error and a higher percentage of eyes with prediction errors within ±0.25 D, ±0.50 D, and ±1.00 D, which was congruent with our findings. [18] In our study, the Barrett Universal II formula had the lowest median absolute error (0.263) and a higher percentage of eyes with prediction errors within ±0.50 D, ±0.75 D, and ±1.00 D compared to the other formulas.…”
Section: Discussionsupporting
confidence: 84%
“…[8,15,16] The Barrett Universal II formula was recently introduced and its accuracy has been studied, and better refractive outcomes than those of other formulas have been reported. [14,16,[17][18][19] The newly developed IOLMaster 700 (Carl Zeiss Meditec AG, Jena, Germany) adopted SS-OCT technology and recently integrated the latest-generation Barrett IOL power calculation formulas. Therefore, cataract surgeons can automatically apply this formula using this device.…”
Section: Introductionmentioning
confidence: 99%
“…3) Many research papers studying the accuracy of the predictability of different IOL calculation formulas have been published. 4,5) Most researchers state that Barrett Universal II is one of the most reliable IOL calculation formulas. 4,5) Some studies have analyzed the influence of preoperative anterior chamber depth (ACD) on PPR in different IOL calculation formulas.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Most researchers state that Barrett Universal II is one of the most reliable IOL calculation formulas. 4,5) Some studies have analyzed the influence of preoperative anterior chamber depth (ACD) on PPR in different IOL calculation formulas. 6,7) They concluded that the influence of preoperative of ACD on PPR varies from formula to formula.…”
Section: Introductionmentioning
confidence: 99%
“…Published results would suggest that surgeons are, by and large, meeting expectations . Refractive outcomes remain variable based upon differences in surgeon technique and experience, preoperative diagnostic technology and the population cohort . Proposed benchmark outcomes also vary.…”
Section: Discussionmentioning
confidence: 99%